Scientific analysis of the sales funnel and customer behavior based on the aida model in digital marketing strategies - Jurayeva Saltanat Khojayorovna (THE INNOVATION ECONOMY, 2026)
This article explores the application of the AIDA model (Attention, Interest, Desire, Action) in Uzbekistan’s digital marketing strategies, analyzing sales funnel stages and customer segmentation to optimize sales. Furthermore, it evaluates the effectiveness of advertising campaigns through CPA and CPL metrics and discusses strategies for building a loyal customer base.